História na educação matemática: uma proposta para o ensino de medidas no ensino fundamental - Ilma Ribeiro Linhares (2016)
This work presents the description of a study in which was tried to analyze the possible relations between the history of mathematics and the solving of problems in teaching measures. It was done in a class of sixth grade students of a public Elementary School. The study was interlined in a qualitative analysis, having its support on the theorical referentials about the solving of problems, as well as the use of the history of mathematics in the classroom. In this study we evidence that the History of Mathematics when used in classroom, becomes a major pedagogical resource, able to contribute in order to qualify the teaching-learning process or mathematics to beyond an instrument of pure motivation. This way, in our conclusion, its necessary that the teacher have conditions and knowledges to implant this resource in his or her classes, making it possible to the students a view that Mathematics is a developing and contextualized subject.